Feasibility Analysis of the 40 MWp Tembesi Floating Solar Power Plant Development Project - Muhammad Ariansyah Putra; Eri Prabowo (Journal La Multiapp, 2026)
This study aims to analyze the feasibility of the Tembesi Floating Solar Power Center (PLTS) construction project with a capacity of 40 MWp in the Batam - Bintan electricity system. The financial feasibility includes calculation of investment costs, operation and maintenance costs, and cost benefit analysis using indicators such as Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period. The operational feasibility analysis includes alternatives to achieving goals, assessment of how to achieve goals, scope of work, and conclusions of the operational feasibility study. The results showed that the construction of a floating solar power plant in Tembesi Reservoir is technically feasible. The proposed design and technology are capable optimal performance of the floating solar PV system, ensuring effective and efficient operations. Financial analysis, including consideration of sensitivities and assumptions, shows that the project is financially viable. The project has an internal rate of return (IRR) that meets the investment feasibility requirements. The rates are 8.82 cUSD/kWh if the power is evacuated through 150 kV lines, and 7.96 cUSD/kWh if evacuated through 20 kV lines. Based on the analysis, the construction of 40 MWp Tembesi Floating Solar Power Plant electricity system is declared feasible to be implemented.